Evaluating the critical strain energy release rate of bioactive glass coatings on Ti6Al4V substrates after degradation. (February 2018) - Matinmanesh, A.; Li, Y.; Nouhi, A.; Zalzal, P.; Schemitsch, E.H.; Towler, M.R.; Papini, M.
Abstract: It has been reported that the adhesion of bioactive glass coatings to Ti6Al4V reduces after degradation, however, this effect has not been quantified. This paper uses bilayer double cantilever (DCB) specimens to determine G IC and G IIC, the critical mode I and mode II strain energy release rates, respectively, of bioactive coating/Ti6Al4V substrate systems degraded to different extents. Three borate-based bioactive glass coatings with increasing amounts of incorporated SrO (0, 15 and 25 mol%) were enamelled onto Ti6Al4V substrates and then immersed in de-ionized water for 2, 6 and 24 h. The weight loss of each glass composition was measured and it was found that the dissolution rate significantly decreased with increasing SrO content. The extent of dissolution was consistent with the hypothesis that the compressive residual stress tends to reduce the dissolution rate of bioactive glasses. After drying, the bilayer DCB specimens were created and subjected to nearly mode I and mode II fracture tests. The toughest coating/substrate system (one composed of the glass containing 25 mol% SrO) lost 80% and 85% of its G IC and G IIC, respectively, in less than 24 h of degradation. The drop in G IC and G IIC occurred even more rapidly for other coating/substrate systems. Therefore, degradation of borate bioactive glass coatings is inversely related to their fracture toughness when coated onto Ti6A4V substrates. Finally, roughening the substrate was found to be inconsequential in increasing the toughness of the system as the fracture toughness was limited by the cohesive toughness of the glass itself. Graphical abstract: